A multidisciplinary investigation into "playing-up" in academy football according to age phase - Kelly, A.; Wilson, M. R.; Jackson, D. T.; Goldman, D. E.; Turnidge, J.; Côté, J.; Williams, C. A. (Journal of Sports Sciences, 2021)
In an attempt to facilitate more appropriate levels of challenge, a common practice in academy football is to play-up talented youth players with chronologically older peers. However, the context of playing-up in academy football is yet to be empirically explored. Thus, the purpose of this study was to examine the multidimensional factors that differentiated players who play-up from those who do not. Ninety-eight participants from a single football academy were examined within their age phase: Foundation Development Phase (FDP; under-9 to under-11; n = 40) and Youth Development Phase (YDP; under-12 to under-16; n = 58). Drawing upon the FA Four Corner Model, 27 factors relating to Technical/Tactical, Physical, Psychological, and Social development were assessed. Following MANOVA analysis within both the FDP and YDP, significant differences were observed for Technical/Tactical and Social sub-components (P < 0.05). Further differences were observed for Physical and Psychological sub-components (P < 0.05) within the YDP. In sum, Technical/Tactical and Social characteristics appeared to differentiate those who play-up compared to those who do not within the FDP. In the YDP however, there were measures representing all sub-components from the FA Four Corner Model. Subsequently, it is suggested coaches and practitioners consider these holistic factors when playing-up youth football players within relevant age-phases.